2016
DOI: 10.1007/s00198-016-3769-2
|View full text |Cite
|
Sign up to set email alerts
|

Biologic therapies and bone loss in rheumatoid arthritis

Abstract: Treatment with biologic drugs is associated with the decrease in bone loss. Studies with anti-TNF blocking agents show preservation or increase in spine and hip BMD and also a better profile of bone markers. Most of these studies were performed with infliximab. Only three epidemiological studies analyzed the effect on fractures after anti-TNF blocking agent's treatment. IL-6 blocking agents also showed improvement in localized bone loss not seen with anti-TNF agents. There are a few studies with rituximab and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
130
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(137 citation statements)
references
References 117 publications
2
130
1
4
Order By: Relevance
“…67 The underlying mechanism most likely involves a TNF-a-dependent activation of osteoclastogenesis, 68,69 leading to osteopenia and bone resorption. Moreover, anti-TNF-a treatment also helps to prevent bone resorption in patients with RA and inflammatory bowel disease 30,31,70,71 and in inflammatory arthritis models in mice. 72,73 Interestingly, unilateral osteopenia adjacent to the injured knee can occur in patients following ACL injury, 67,74 raising questions about a possible role for TNF-a in this process.…”
Section: Discussionmentioning
confidence: 99%
“…67 The underlying mechanism most likely involves a TNF-a-dependent activation of osteoclastogenesis, 68,69 leading to osteopenia and bone resorption. Moreover, anti-TNF-a treatment also helps to prevent bone resorption in patients with RA and inflammatory bowel disease 30,31,70,71 and in inflammatory arthritis models in mice. 72,73 Interestingly, unilateral osteopenia adjacent to the injured knee can occur in patients following ACL injury, 67,74 raising questions about a possible role for TNF-a in this process.…”
Section: Discussionmentioning
confidence: 99%
“…(38)(39)(40)(41) Additionally, use of anti-TNFa medication in patients with chronic inflammatory states, such as RA or AS, has been shown to decrease bone resorption, increase bone formation, prevent erosion formation in RA patients (which is due to osteoclast-mediated bone destruction), and decrease bone loss. (18,19) Although acute activation of NF-kB following stress or injury is critical for healing, (42) a sustained activation of TNFa and sTNFa-R1 level can potentially disturb the balance between osteoblast (cells involved in bone formation) and osteoclast (cells involved in bone resorption) activity through increased production RANKL, favoring bone resorption. (43) Cauley and colleagues (44) revealed that an elevated serum level of sTNFa-R1 was associated with increased incidence of fracture in men.…”
Section: Discussionmentioning
confidence: 99%
“…For clinical purposes, soluble TNFα‐R1 (sTNFα‐R1) with its long‐term bioavailability in stored serum is an optimal proxy of activated TNFα and a biomarker of systemic inflammation. Moreover, clinical data using TNF inhibitors in patients with rheumatoid arthritis (RA) or axial spondyloarthritis (AS) have shown improvements in bone metabolite profiles and decreases in bone loss . Thus, we chose sTNFα‐R1 as a biomarker of inflammation for this study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies reported that blocking the function of Dkk-1 benefited bone maintenance and protected from systemic bone loss[5, 6]. Current opinions on osteoporosis realized that DKK1 level was associated with the pathophysiology of postmenopausal osteoporosis[7, 8], and with the inflammatory cytokines effects on bone mass[9, 10]. Ahmed et al showed postmenopausal women with significantly increased serum Dkk-1 had more severe osteoporosis, indicating that higher level of serum Dkk-1 might act as a biomarker for the development and severity of osteoporosis[7].…”
Section: Introductionmentioning
confidence: 99%